2018
DOI: 10.1038/s41419-018-1259-5
|View full text |Cite
|
Sign up to set email alerts
|

Midostaurin potentiates rituximab antitumor activity in Burkitt’s lymphoma by inducing apoptosis

Abstract: An intensive short-term chemotherapy regimen has substantially prolonged the overall survival of Burkitt’s lymphoma (BL) patients, which has been further improved by addition of rituximab. However, the inevitable development of resistance to rituximab and the toxicity of chemotherapy remain obstacles. We first prepared two BL cell lines resistant to rituximab-mediated CDC. Using a phosphorylation antibody microarray, we revealed that PI3K/AKT pathway contained the most phosphorylated proteins/hits, while apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Recently, the chemotherapy agents doxorubicin (DNR), mitoxantrone (Mito), etoposide or 2‐aminopurine‐6‐thiol (6‐TG) have become the preferred choices for AML treatment . Meanwhile, molecular‐targeted agents, eg midostaurin or enasidenib, have been approved for AML treatment and brought new hope for AML patients . Midostaurin, developed by Novartis Corporation, targets FLT3, c‐KIT, PDGFRB, VEGFR‐2 or protein kinase C; enasidenib, developed by Agios Corporation and Celgene Corporation, targets isocitrate dehydrogenase 2 (IDH2) to specifically inhibit the function of IDH2 mutants, reduces 2‐HG levels and reverses genomic hypermethylation status of AML .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the chemotherapy agents doxorubicin (DNR), mitoxantrone (Mito), etoposide or 2‐aminopurine‐6‐thiol (6‐TG) have become the preferred choices for AML treatment . Meanwhile, molecular‐targeted agents, eg midostaurin or enasidenib, have been approved for AML treatment and brought new hope for AML patients . Midostaurin, developed by Novartis Corporation, targets FLT3, c‐KIT, PDGFRB, VEGFR‐2 or protein kinase C; enasidenib, developed by Agios Corporation and Celgene Corporation, targets isocitrate dehydrogenase 2 (IDH2) to specifically inhibit the function of IDH2 mutants, reduces 2‐HG levels and reverses genomic hypermethylation status of AML .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, molecular‐targeted agents, eg midostaurin or enasidenib, have been approved for AML treatment and brought new hope for AML patients . Midostaurin, developed by Novartis Corporation, targets FLT3, c‐KIT, PDGFRB, VEGFR‐2 or protein kinase C; enasidenib, developed by Agios Corporation and Celgene Corporation, targets isocitrate dehydrogenase 2 (IDH2) to specifically inhibit the function of IDH2 mutants, reduces 2‐HG levels and reverses genomic hypermethylation status of AML . However, as clinical practical experience is accumulating, these agents have not led to the hoped‐for improvements in the survival of or prognosis for AML patients, suggesting that kinase inhibition may exert mild effects at the beginning of tumor development but lose its effect early on.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, PDX BL models were generated from affected patient lymph nodes in athymic nude and SCID mice, demonstrating metastatic potential in SCID mice, but not in athymic nude mice 125 . These models have been used to study novel agents such as the pan-protein kinase C (PKC) inhibitor midostaurin with and without rituximab 71 , 126 . Promising results in preclinical models have led to ongoing clinical trials 71 .…”
Section: Xenograft Models In Non-hodgkin Lymphomamentioning
confidence: 99%
“…These models have been used to study novel agents such as the pan-protein kinase C (PKC) inhibitor midostaurin with and without rituximab 71 , 126 . Promising results in preclinical models have led to ongoing clinical trials 71 .…”
Section: Xenograft Models In Non-hodgkin Lymphomamentioning
confidence: 99%
“…In the process of TGF-β-induced epithelial–mesenchymal transition (EMT), CD59 is significantly upregulated by Smad3 to evade complement-mediated attack in metastasis ( 26 ). Further, we also found that the PKC signaling pathway is significantly activated in rituximab-resistant Burkitt’s lymphoma (BL) cells, and the application of the PKC inhibitor midostaurin could significantly enhance the pro-apoptotic effect of rituximab, leading to a significant therapeutic effect in tumor-bearing mouse models ( 27 ). Here, we demonstrate that NF-κB signaling axis is responsible for inducible CD59 expression in rituximab-resistant B-NHL cells and that inhibition of this axis can reduce CD59 expression and consequently sensitize rituximab-resistant B lymphoma cells to CDC effect.…”
Section: Introductionmentioning
confidence: 99%